Teacher Experience In Using Sgd to Teach Writing: A Narrative Inquiry - Ramadhani Syuhada Al Rasyid (Jurnal Ilmiah Wahana Pendidikan, 2026)
This Research explore the experience of an English teacher in implementing Small Group Discussion (SGD) to teach writing in EFL Junior Highschool, Using qualitative method with narrative inquiry approach, this study highlighted how the subject with over 13 years of teaching experience utilizes vocabularies building, and skill based student grouping to improve classroom participation. The findings indicated that the subject started his teaching with daily vocabulary exercise, followed by student collaboration in suitable groups that support and develope their writing skills. the teacher’s ability to motivate learners and adapt the teaching program to students' needs plays a crucial role in the effective implementation of SGD. These insights align with previous studies by Setiawan and Wulansari (2020) as well as Larasati (2023), emphasizing the importance of foundational vocabulary, targeted grouping, and flexible instructional design. This research found that the subject of this research use a more specified grouping to further increases students activeness in the classroom. Grouping according the students skill level, according to the subject, could increases the participation of students in the classroom.